Effect of omega-9 rich fish oil on antioxidant enzymes and relative immune gene expressions in Nile tilapia (Oreochromis niloticus) - Doungporn Amornlerdpison (2020)
© 2019, Prince of Songkla University. All rights reserved. Freshwater fish oil (FFO) was extracted from by-products of the fisheries industry. The amounts of omega-3, 6, and 9 fatty acids in the FFO were 1.38, 12.29, and 42.9 g/100 g, respectively. The diet of Nile tilapia was supplemented with FFO for 4 months to evaluate the effect of FFO on gene expression of antioxidant enzymes and growth-associated immune response. Nile tilapia supplemented with 1% and 1.5% FFO demonstrated growth. Gene expression of antioxidant enzymes including super-oxide dismutase, catalase, and glutathione and cytokines of immunity, including TNF-α, IL-1β, and IgM were determined. Three antioxidant enzymes and immune cytokines in the liver tissue were not statistical different among the experimental groups, but expression of GPx and IgM increased in the kidneys of the FFO-supplemented Nile tilapia. IL-1β gene expression in the kidneys also significantly increased. This indicated that the proinflammatory cytokine IL-1β might be enhanced by omega-6 fatty acid. FFO supplemented in fish feed can improve growth, but the related immune gene expressions remain unclear.